Persecution and Toleration in the English Reformation - Elton, G. R. (Studies in church history, 1984)
The century of the Reformation, in England as elsewhere, sharpened all conflicts and augmented persecution. As the unity of Christendom broke up, the rival parties acquired that sort of confidence in their own righteousness that encourages men to put one another to death for conscience sake; an era of moderation and tolerance gave way to one of ever more savage repression. To the openminded willingness which characterized the humanism of Erasmus and More as well as the Rome of Leo X there succeeded the bigotry typical of Carafa, Calvin, Knox and the English puritans; only the gradual evaporation of such passions, produced by each side’s inability to triumph totally, produced a weariness with religious strife which made the return of mutual sufferance possible. That, at least, is the received story. Historians of toleration, as for instance Jordan and Lecler, firmly described the history of persecution in this way. Jordan identified six developments which led to its decline in sixteenth-century England: a growing political strength among dissident sects, the impossibility of preventing splintering and preserving uniformity, the needs of trade which overrode religious hostility, experience of travel, the failure to suppress dissident publications, and finally a growing scepticism which denied the claims to exclusive truth advanced by this or that faction. In other words, only two things moved men, once they had fallen away from the generosity of the pre-Reformation era, to substitute an uneasy toleration for a vigorous persecution: the external pressures of experience and the decline of religious fervour. By implication, men of power called for repression and only those who could not hope to win favoured toleration, until general exhaustion set in. It is a convincing enough picture, and much evidence no doubt supports it. But it is a picture—a general and rather schematic panorama which makes little allowance for the real opinions of individuals. On this occasion I should like to test it by looking at the attitudes of two highly articulate sixteenth-century Englishmen—Thomas More, humanist and loyal son of the universal Church, and John Foxe, humanist and faithful protestant. Both, we know, were men of sensitivity and sense. How did they stand to the problem of persecution?